Examining the Relationship between Transformational Leadership and Organizational Citizenship Behavior among the Lecturers of Higher Institutions in Katsina State Nigeria - Salisu, Abba Yangaiya (Journal of Islamic Economics and Social Science (JIESS), 2022)
The study is aim at examining the relationship between transformational leadership (TL) and organizational citizenship behavior (OCB) among the lecturers of higher institutions in Katsina state Nigeria. Four hundred and three participants were used in this study. The study used transformational leadership and organizational citizenship behavior questionnaires to get the needed data. Both questionnaires were adopted and adapted. Descriptive statistics and multiple regression analyses were employed to analyze the data collected using Special Package for Social Science Research (SPSS) version 20. The findings indicate that there are significant and positive relationship between transformational leadership and organizational citizenship behavior of lecturers of higher institutions in Katsina state (R2 .43). The findings bring to the fore the need for the heads of institutions of higher learning to enhance the lecturer’s organizational citizenship behavior by full application of transformational leadership practices in their respective institutions. The findings add to the existing literature on leadership especially in Nigeria where little was written on the area.